GROUND RENT IN VIEW OF ACCOUNTING - Elena A. Shelukhina (Вестник Северо-Кавказского федерального университета, 2022)
The item is focused on the issue and types of ground rent as well as some methodological aspects of ground-rent accounting in order to justify the basis of drawing a line between differential and ecological rent as subjects of accounting depending on the economic ways of employing the ground-capital.